THE ROLE OF MINANGKABAU CULTURAL VALUES IN HR DEVELOPMENT - Efrizon Efrizon; Masydzulhak Djamil Mz; Sugeng Santoso; Ahmad Badawi (Jurnal Ekonomi, 2022)
This literature review reveals the important role of cultural values ​​and indigenous knowledge of the local community (Indigenous people) in sustainable development and human resource development for resource excellence. Each community has developed its own complex practices to protect and to manage its natural resources and ecosystems. The Minangkabau community is known as a contributor to intellectuals who played an important role in the history of the nation and state, especially in the pre-independence period and at the beginning of independence. The success of the Minangkabau people in producing national figures who bear the name of the nation and state has made Minangkabau one of the intellectually producing societies in the country. Indigenous knowledge and traditional values ​​and culture of the Minangkabau people have been used and developed for a long time in the social structure of their society. Cultural values ​​and indigenous knowledge or local wisdom are social capital as the embodiment of traditional cultural elements that are deeply rooted, in human and community life related to human resources, cultural resources, economy, security and law.